Returning to Memory An Exhibition of Oracle Bone Script - Li, Yaxiao (Auckland University of Technology, 2019)
Oracle bone script was the earliest form of Chinese characters carved on turtle plastrons and animal bones using a sharp tool. Oracle bone script was used for divination through fire in the Shang dynasty (c.1600-1046 BCE). This research explores ways to promote and enhance audience interest in the script through storytelling strategies that use interactive technology in an exhibition context. Through the course of this study, I found that there is a lack of publicity and cultural engagement with oracle bone script and that this has contributed to the general public knowing little about its historical importance. Therefore, I have created a proposal for an exhibition that showcases, through various means, this significant Chinese historical legacy.
Keywords: Oracle bone script; Exhibition design; Storytelling; Interactive technology